Relations Between Irāḳ Seljuk State and ʿAbbāsīd Khalīfate According to Tajaribu’s-Salaf - Pınar Kaya Tan (Şarkiyat Mecmuası)
Hindū-shāh as-Sahibî an-Nakhčiwānī (d. 730/1329–1330), one of the 14th century historians, men of letters and scholars, wrote his Persian historical book Tajaribu’s-Salafder Tawarikhi’l-Khulafa wa’l-Wuzara after 724 (1324), when he was in the service of Nuṣratu’d-Dīn Aḥmad b. Yūsufshah (695–733/1296–1333), one of the Atabakan of Luristan, The work, which contains information about the ʿAbbāsīd Khalīfas and the viziers who served with them, undoubtedly contains detailed information about the neighboring dynasties that had close contact with the ʿAbbāsīd Khalīfate. In this respect one of the states written down in the work is the Irāḳ Seljuk State (511–590/1118–1194). Especially due to its close location to Baghdād, the center of the khalīfate, the relations between the two states and the power struggles that sometimes occurred are frequently discussed in the work. In this study, the relations between the Irāḳ Seljuk State and the ʿAbbāsīd Khalīfate will be examined in the light of the information given by Hindū-shāh as-Sahibî and the information conveyed by the author will be evaluated by comparing it with the narrations of contemporary sources.